Troubling Tonsils! - Reynolds, Aaron, 1970-; Brown, Peter, 1979- (New York : Simon & Schuster Books for Young Readers, 2025)
Jasper Rabbit tells the eerie tale of Charlie Marmot, whose decision to keep his tonsils after surgery leads to creepy, mysterious events.
new kids book 2025 fall.
Ages 6 to 9
Grades 2-3
Keywords: Horror; Tonsils -- Fiction; Marmots -- Fiction; Rabbits -- Fiction; JUVENILE FICTION / Horror; Animal fiction; Animal fiction; Horror fiction